Analysis of Exploratory Data For The Interactive Visualization Gap - Ravi Kumar, Md. Talib Ahmad, Niraj Kumar, Md Shahid Ahmad (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Complexity is one of the defining features of data scaling. When it comes to big data and data integration, heterogeneous data is a major factor. Both are necessary, but enormous amounts of data processing and storage make it hard to see and understand big databases. Data extraction in a way that the human brain can understand is a major challenge in this data-driven era of exponential data growth. This study summarizes and offers a description of heterogeneous distributed storage, data visualization, and the difficulties associated with it, drawing on a variety of approaches from prior studies. In addition, we compare the findings of the examined research works and talk about the major change happening in the field of virtual reality huge data visualization.